Website-based National University Employee Data Administration Design: Website-based National University Employee Data Administration Design - Muhammad Reza Akbar; Septi Andryana; Aris Gunaryati (Jurnal Mantik, 2020)
Data storage that is done carefully will produce valid data that is good and useful for the user. this careful data storage certainly must be adjusted to a good data storage. Don't have data that has turned out well to be useful for the user. Data management and information storage media related to data, biodata, and employee activities are still done manually. Managing data manually is ineffective and a waste of time, when data collection is not effective employee data. This research was made for the National University, this Web-based System as a medium for information, the programs used are HTML, PHP, Composer, and PostgreSQL databases, hopefully managing data like this can facilitate the Admin in managing employee data efficiently and effectively.